SELECTED ASPECTS OF SHAPING THE COMPETENCE OF CIVIL AND MILITARY AIR TRANSPORT CREW USING CREW RESOURCE MANAGEMENT (CRM) TRAINING - Grzegorz KUŁAKOWSKI; Henryk NOWAKOWSKI (Scientific Journal of Silesian University of Technology. Series Transport)
In this article, the Crew Resource Management (CRM) is described as an important element of the flight safety system aimed at preparing and supplying the aircraft crews with the necessary knowledge and competencies in the area of personal and group performances and limitations (Human Factor – HF). It also presents the CRM training requirements for both flight and cabin personnel in commercial aviation, as well as selected issues regarding the training of the military aviation personnel in the field of human factors and CRM. This paper identifies the common CRM training areas in the field of civil and military, and also presents the fundamental differences and challenges faced by the military aviation in the area of CRM training, based on one of the five key factors of the “5M model” by James Reason influencing the aviation incidents – “Media” (Environment).